2014
DOI: 10.1155/2014/819528
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic Acidosis and Strong Ion Gap in Critically Ill Patients with Acute Kidney Injury

Abstract: Purpose. To determine the influence of physicochemical parameters on survival in metabolic acidosis (MA) and acute kidney injury (AKI) patients. Materials and Methods. Seventy-eight MA patients were collected and assigned to AKI or non-AKI group. We analyzed the physiochemical parameters on survival at 24 h, 72 h, 1 week, 1 month, and 3 months after AKI. Results. Mortality rate was higher in the AKI group. AKI group had higher anion gap (AG), strong ion gap (SIG), and apparent strong ion difference (SIDa) valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
(25 reference statements)
1
12
0
2
Order By: Relevance
“…For patients with STEMI, AG was proved to be an independent risk factor for high inhospital mortality after percutaneous coronary intervention and could be used for risk stratification [ 14 ]. Moreover, a meta-analysis and another study revealed that AG may be a good choice to assess the prognosis of critically ill patients especially for those in areas with inadequate medical resources [ 15 , 28 ]. Similarly, our data suggested that AG was associated with inhospital all-cause mortality of CCU patients independently, and maybe the adverse effects of increased AG on coronary artery disease and critically ill patients contribute to this result.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with STEMI, AG was proved to be an independent risk factor for high inhospital mortality after percutaneous coronary intervention and could be used for risk stratification [ 14 ]. Moreover, a meta-analysis and another study revealed that AG may be a good choice to assess the prognosis of critically ill patients especially for those in areas with inadequate medical resources [ 15 , 28 ]. Similarly, our data suggested that AG was associated with inhospital all-cause mortality of CCU patients independently, and maybe the adverse effects of increased AG on coronary artery disease and critically ill patients contribute to this result.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were found to have mixed acid-base disorders due to hyperchloremia and hypoalbuminemia, in spite of normal blood gas parameters [182]. Zheng and colleagues [183] studied 78 patients with metabolic acidosis with or without acute kidney injury (AKI). They analyzed physicochemical parameters at 24 and 72 h, at 1 week, 1 month, and 3 months on survival after AKI.…”
Section: Quantitative Acid-base Analysis: the Strong Ion Gapmentioning
confidence: 99%
“…While AG predicts short-term mortality, strong ion gap predicts both short- and long-term mortality, in AKI patients with metabolic acidosis. [ 31 ] However, apart from lactate, there is no consensus about the clinical relevance of individual components of metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%